Federal Government Human Health PFAS Research Workshop: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Per- and polyfluoroalkyl substances (PFAS) are human-made substances used in thousands of products, from medical devices to fire-fighting foam to oil- and stain-resistant coatings on carpets and packaging. They help make these products resistant to heat, water, stains, and grease. However, research over the past several decades has found evidence that PFAS persist in the environment for long periods of time, potentially leading to harmful human exposures. To review federal agency human health PFAS research and identify research and data gaps, the Environmental Protection Agency, with support from the U.S. Department of Agriculture, Department of Defense, and Department of Health and Human Services, requested that the National Academies of Sciences, Engineering, and Medicine convene a workshop. The workshop, which was held on October 26-27, 2020, addressed topics including the federal context for PFAS research, human exposure, experimental toxicology, human health outcomes, and cross-cutting issues in PFAS risk assessment. This publication highlights the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

Review of the Revised NTP Monograph on the Systematic Review of Fluoride Exposure and Neurodevelopmental and Cognitive Health Effects: A Letter Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
In 2019, the National Toxicology Program (NTP) released the draft monograph Systematic Review of Fluoride Exposure and Neurodevelopmental and Cognitive Health Effects. Given the controversies surrounding the risks and benefits associated with fluoride exposure and to ensure the integrity of its evaluation, NTP asked the National Academies of Sciences, Engineering, and Medicine to review the draft monograph. The 2020 report Review of the Draft NTP Monograph Systematic Review of Fluoride Exposure and Neurodevelopmental and Cognitive Health identified deficiencies in the analysis of various aspects of some of the studies and in the analysis, summary, and presentation of the data in the draft monograph, provided many suggestions for improvement, and concluded that NTP had not adequately supported its conclusions. At the request of NTP, Review of the Revised NTP Monograph on the Systematic Review of Fluoride Exposure and Neurodevelopmental and Cognitive Health Effects determines whether substantive concerns raised in the 2020 report have been sufficiently addressed by revisions of the monograph and whether the evidence presented by NTP in the revised monograph supports its conclusions.
Keywords: Environment and Environmental Studies

How We Move Matters: Exploring the Connections Between New Transportation and Mobility Options and Environmental Health: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Recent years have brought dramatic changes to the ways people and goods move around their communities. Many of these changes have important ramifications - for better or worse - for human health, equity, pollution, and climate. The workshop How We Move Matters: Exploring the Connections Between New Transportation and Mobility Options and Environmental Health, held over three virtual sessions from July 13-21, 2021, provided a forum to discuss these developments, consider the risks and benefits, and identify opportunities to chart a healthier and more equitable mobility future.
Keywords: Environment and Environmental Studies

The Use of Systematic Review in EPA's Toxic Substances Control Act Risk Evaluations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Systematic review - a scientific investigation that focuses on a specific question and uses explicit, prespecified scientific methods to identify, select, assess, and summarize the findings of similar but separate studies - has become the foundation for assessing evidence to be used for decision making in a variety of health contexts, including health care and public health. At the request of the Environmental Protection Agency (EPA), this publication reviews EPA's 2018 guidance document Application of Systematic Review in TSCA (Toxic Substances and Control Act) Risk Evaluations and associated materials to determine whether the process is comprehensive, workable, objective, and transparent.
Keywords: Environment and Environmental Studies

Quality Water from Every Tap: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The quality of U.S. drinking water is at risk from many causes, including the nation's aging infrastructure and environmental conditions that affect source water conditions. Quality Water from Every Tap, a workshop held in Washington, D.C., on November 21-22, 2019, provided an opportunity for experts from government, affected communities, academia, and the private sector to explore both the challenges and factors that affect the delivery of water with acceptable quality and the paths to increase the quality of water for systems that do not meet today's drinking water standards - especially focusing on communities that lack adequate resources and expertise because they are small or have declining populations. This publication provides the rapporteurs' high-level summary of the topics addressed in the workshop and suggestions provided by workshop participants for potential actions to address the nation's water quality challenges.
Keywords: Environment and Environmental Studies

Perspectives on Climate and Environmental Justice on the U.S. Gulf Coast: Proceedings of a Webinar–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Communities along the Gulf Coast routinely experience intense weather events. Acute and repetitive shocks - illustrated by the multiple Gulf regional hurricane landfalls during the 2020 hurricane season - have a disproportionate impact on communities in this region that are already burdened by chronic stressors such as systemic and structural racism, poverty, environmental degradation, and health disparities. Climate change threatens to exacerbate the severity of these impacts as disadvantaged and underserved communities fall further behind in their ability to prepare for, respond to, mitigate, or recover from disasters. On June 24, 2021, the Gulf Research Program of the National Academies of Sciences, Engineering, and Medicine convened a panel of three members of the White House Environmental Justice Advisory Council to discuss steps that are being taken or that need to occur to advance climate and environmental justice for those who call the Gulf of Mexico region home. The panelists discussed opportunities to equitably improve conditions in the Gulf of Mexico region, particularly within Black, Indigenous, and People of Color communities. This event provided important perspective, though much work remains to elevate and examine the climate and environmental justice priorities of diverse communities, particularly Indigenous people, and to identify the mechanisms necessary to implement the recommendations offered by the panel members. This publication summarizes the discussion.
Keywords: Environment and Environmental Studies

Pivotal Interfaces of Environmental Health and Infectious Disease Research to Inform Responses to Outbreaks, Epidemics, and Pandemics: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Pathogens are the cause of infectious diseases, but the environment can play an important role in influencing the conditions under which pathogens spread and cause harm. Understanding the complex interplay among people, pathogens, and the environment - broadly encompassing the chemical, biological, physical, and social surroundings - can lead to a more complete picture of where and how infectious diseases emerge, how they spread, and how to respond to outbreaks. The virtual workshop Pivotal Interfaces of Environmental Health and Infectious Disease Research to Inform Responses to Outbreaks, Epidemics, and Pandemics was held on June 8-9, 2021. This workshop provided a venue for experts in infectious diseases, environmental health, and data science from government, academia, and the private sector to examine current knowledge about the environment-infectious disease interface and to explore how this knowledge can be used to inform public health decisions. Key workshop topics included how advances in environmental exposure assessments can be applied to identify, predict, and monitor critical infectious disease exposure pathways, and how climate and environmental modeling techniques can be applied to better understand the biology and transmission dynamics of pathogens and provide early warning of emerging threats. In addition, workshop sessions explored critical data gaps at the environment-infectious disease interface and provided insight on how new and emerging techniques can be applied to address those data gaps, especially through the integration of tools used in environmental health and infectious disease research. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

Leveraging Advances in Remote Geospatial Technologies to Inform Precision Environmental Health Decisions: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Leveraging Advances in Remote Geospatial Technologies to Inform Precision Environmental Health Decisions, a virtual workshop held on April 14-15, 2021, explored how advances in geospatial technologies can inform precision environmental health, the targeted public health interventions that reach the right populations at the right time. The workshop was organized by a planning committee of the Standing Committee on the Use of Emerging Science for Environmental Health Decisions, a National Academies of Sciences, Engineering, and Medicine program that examines and discusses issues regarding the use of new science, tools, and methodologies for environmental health research and decisions. The workshop included plenary and scientific presentations that focused on technical advances and applications of remote geospatial technologies in environmental health. The workshop was organized around three main sessions: leveraging geospatial technologies to advance environmental justice and health equity; personalizing exposure science to improve environmental health; and geospatial science for preparing for and responding to environmental disasters. The workshop's final session centered on breakout discussions on major cross-cutting themes including data availability; data integration; training and capacity building; and privacy and ethics. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies

Reducing the Health Impacts of the Nitrogen Problem: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Nitrogen fertilizer is used extensively in the United States to maximize crop yields. As an essential nutrient to plant growth, nitrogen is a critical input to enhance agricultural productivity. However, excess nitrogen can leach into soil and water and contaminate drinking water sources with nitrate, a water-soluble chemical compound of nitrogen. Too much nitrate consumption can pose a health risk. Users of public drinking water supplies and private wells in areas surrounded by farmland are particularly vulnerable to exposure to nitrate in their drinking water. The workshop Reducing the Health Impacts of the Nitrogen Problem, held over five weekly virtual sessions from January 28 to February 25, 2021, provided a venue to discuss opportunities for reducing exposure to nitrate from agricultural sources in drinking water. More than 50 experts with backgrounds in agriculture, public health, economics, policy, engineering, water, social science, and other fields shared their perspectives through presentations and moderated discussions. This Proceedings of a Workshop-in Brief provides the rapporteurs' high-level summary of the topics and suggestions for potential actions to address challenges surrounding human exposure to nitrate from agricultural sources through drinking water, as discussed at the workshop itself.
Keywords: Environment and Environmental Studies

Sustainable and Resilient Supply Chains Using Emerging Technologies: Policy Options: Proceedings of a Workshop–in Brief - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The coronavirus disease 2019 (COVID-19) crisis sparked concerns about the vulnerability of supply chains and the significant impact of their disruption on the economy and society within the U.S. and abroad. Issues around global supply chains existed before the pandemic but were also greatly aggravated by it. To consider these issues, the Science and Technology for Sustainability program, in collaboration with the Resilient America Program, Transportation Research Board, and Board on Atmospheric Sciences and Climate at the National Academies of Sciences, Engineering, and Medicine, held a series of four virtual workshops on February 3, 4, 17, and 18, 2021. The workshop series addressed opportunities, challenges and environmental implications of increasing local inclusion and community participation in global value chain networks by using new technologies to strengthen resilience and sustainability in the face of recurring disruptions. The series also explored the feasibility of introducing advanced manufacturing, logistics and decision-making under alternative supply chain scenarios in different sectors, with a view to strengthening the resilience of communities and adopting far more environmentally and economically sustainable consumption and production approaches. This publication summarizes the presentations and discussion of the workshops.
Keywords: Environment and Environmental Studies

The Interplay Between Environmental Exposures and Mental Health Outcomes: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Mounting evidence shows that the environment can play an important role in mental health, yet comparatively few studies have focused on the mental or behavioral health outcomes of environmental stressors. The Interplay Between Environmental Exposures and Mental Health Outcomes, a virtual workshop held on February 2-3, 2021, provided mental health and environmental health research experts from government, academia, and the private sector with the opportunity to explore emerging research on the relationships between environmental exposures and mental health. Workshop presentations covered a broad array of the diverse makeup of environmental exposures, including those that are chemical, biological, or physical, and either natural or human-made in origin. Furthermore, while the historical definition of an environmental exposure refers to a contact that causes a negative health effect, some presenters highlighted how a person's environment can lead to positive mental health outcomes. Workshop participants also discussed approaches to better integrate mental and behavioral health into multidisciplinary considerations of environmental health; considered how mental and behavioral health impacts could become part of environmental risk assessments and public health choices; and highlighted new tools and technologies to assess ways in which the environment can affect mental health. This Proceedings of a Workshop-in Brief provides the rapporteurs' high-level summary of the topics addressed in the workshop and suggestions provided by workshop participants for ways of integrating mental and behavioral health research and environmental research.
Keywords: Environment and Environmental Studies; Health and Medicine

Progress, Challenges, and Opportunities for Sustainability Science: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on November 30-December 2, 2020 to examine scientific progress and gaps in sustainability science around six cross-cutting themes. These themes include the challenges of measuring progress toward sustainability; promoting equity and justice in sustainability efforts; adapting to change; moving beyond incremental change to transformational change; effectively linking knowledge with decision making; and governance of complex nature-society systems. The workshop was designed to explore opportunities for science to contribute to research-based knowledge in sustainability, and to provide scientific input to the National Academy of Sciences Grand Challenges in Science and the Nobel Prize Summit "Our Planet, Our Future," scheduled for April 2021. Invited speakers from academic institutions around the world were selected by the planning committee to discuss opportunities to contribute to research-based knowledge and use that knowledge in decision-making. Workshop participants included approximately 150 invited scholars and nearly 800 registrants from government, the private sector, academia, and non-governmental sector who viewed the virtual workshop. This proceedings in-brief provides a high-level summary of the presentations and discussions that took place.
Keywords: Environment and Environmental Studies

Effectiveness and Efficiency of Defense Environmental Cleanup Activities of DOE's Office of Environmental Management: Report 1 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The U.S. Department of Energy (DOE) and its predecessor agencies have conducted activities to develop atomic energy for civilian and defense purposes since the initiation of the World War II Manhattan Project in 1942. These activities took place at large federal land reservations of hundreds of square miles involving industrial-scale operations, but also at many smaller federal and non-federal sites such as uranium mines, materials processing and manufacturing facilities. The nuclear weapons and energy production activities at these facilities produced large quantities of radioactive and hazardous wastes and resulted in widespread groundwater and soil contamination at these sites. DOE initiated a concerted effort to clean up these sites beginning in the 1980s. Many of these sites have been remediated and are in long-term caretaker status, closed or repurposed for other uses. Review of the Effectiveness and Efficiency of Defense Environmental Cleanup Activities of the Department of Energy's Office of Environmental Management: First Report provides background information on the sites currently assigned to the DOE's Office of Environmental Management that are undergoing cleanup; discusses current practices for management and oversight of the cleanups; offers findings and recommendations on such practices and how progress is measured against them; and considers the contracts under which the cleanups proceed and how these have been and can be structured to include incentives for improved cost and schedule performance.
Keywords: Environment and Environmental Studies

Progress Toward Restoring the Everglades: The Eighth Biennial Review - 2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
During the past century, the Everglades, one of the world's treasured ecosystems, has been dramatically altered by drainage and water management infrastructure to improve flood management, urban water supply, and agricultural production. The remnants of the original Everglades now compete for water with urban and agricultural interests and are impaired by contaminated runoff from these two sectors. The Comprehensive Everglades Restoration Plan (CERP), a joint effort launched by the state and the federal government in 2000, seeks to reverse the decline of the ecosystem. The multibillion-dollar project was originally envisioned as a 30- to 40-year effort to achieve ecological restoration by reestablishing the natural hydrologic characteristics of the Everglades, where feasible, and to create a water system that serves the needs of both the natural and the human systems of South Florida. In establishing the CERP, Congress also requested that an independent scientific review be conducted on progress toward restoration with biennial reports. The National Academies' Committee on Independent Scientific Review of Everglades Restoration Progress has provided biennial reviews of restoration progress and advice on scientific and engineering issues that may impact progress since 2004. This eighth study of the series describes substantive accomplishments over the past 2 years and reviews developments in research, monitoring, and assessment that inform restoration decision making. Progress Toward Restoring the Everglades: The Eighth Biennial Review - 2020 also reviews the recently developed Combined Operational Plan, which is a prerequisite for CERP progress in the central Everglades, and examines issues facing the northern and southern estuaries, including priorities for science to support restoration decision making.
Keywords: Environment and Environmental Studies; Earth Sciences

Motivating Local Climate Adaptation and Strengthening Resilience: Making Local Data Trusted, Useful, and Used - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Local communities are already experiencing dire effects caused by climate change that are expected to increase in frequency, intensity, duration, and type. Public concern about climate-related challenges is increasing, available information and resources on climate risks are expanding, and cities across the country and the globe are developing approaches to and experience with measures for mitigating climate impacts. Building and sustaining local capacities for climate resilience requires both resilient physical and social infrastructure systems and inclusive, resilient communities. At the request of the Federal Emergency Management Agency, Motivating Local Climate Adaptation and Strengthening Resilience provides guidance for active and ongoing efforts to move science and data into action and to enable and empower applied research that will strengthen capacities for hazard mitigation and resilience in communities, across the nation, and around the world.
Keywords: Environment and Environmental Studies

Partnerships and Cross-Sector Collaboration Priorities to Support Climate Research and Policy: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
As global mean temperatures rise and extreme climate and weather events increase in frequency and intensity, the severity of the climate situation and its potential impacts on human well-being - particularly of the world's most vulnerable populations - is strikingly evident. Research and policy responses to address climate change are required to meet U.S. targets set for the coming decades, which include a reduction of 50 to 52 percent of greenhouse gas emissions by 2030 and net-zero emissions by 2050. In coordination with other activities on climate, energy, and environmental and human health across the National Academies of Sciences, Engineering, and Medicine, the Government-University-Industry Research Roundtable convened a series of five workshops in June and July of 2021 to discuss opportunities for enhancing U.S. scientific and technological approaches to climate research and policy through cross-sector collaboration and partnerships, and to examine the impacts of climate policy on economic development, inequality, and international competitiveness. This document summarizes the presentations and discussions at the five workshops.
Keywords: Policy for Science and Technology; Environment and Environmental Studies

Global Change Research Needs and Opportunities for 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. Global Change Research Needs and Opportunities for 2022-2031 advises the USGCRP on how best to meet its mandate in light of climate change impacts happening today and projected into the future. This report identifies critical climate change risks, research needed to support decision-making relevant to managing these risks, and opportunities for the USGCRP's participating agencies and other partners to advance these research priorities over the next decade.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Radioactive Sources: Applications and Alternative Technologies - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Radioactive Sources: Applications and Alternative Technologies assesses the status of medical, research, sterilization, and other commercial applications of radioactive sources and alternative (nonradioisotopic) technologies in the United States and internationally. Focusing on Category 1, 2, and 3 sources, this report reviews the current state of these sources by application and reviews the current state of existing technologies on the market or under development that are or could be used to replace radioisotopic technologies in those applications. Radioactive Sources will support existing and future activities under the National Nuclear Security Administration Office of Radiological Security program to reduce the use of high-risk radiological materials in commercial applications.
Keywords: Environment and Environmental Studies

The Challenge of Feeding the World Sustainably: Summary of the US-UK Scientific Forum on Sustainable Agriculture - National Academy of Sciences (The National Academies Press, 2021)
The need for sustainable agriculture is becoming ever more significant. The world's population is still increasing, requiring more from our agricultural systems. Malnutrition and diet-related illnesses are present in nearly all societies. At the same time, agriculture plays a significant role in some of the biggest environmental challenges that humanity is facing, including the climate crisis, biodiversity loss, deforestation, and the pollution of our soil, water, and air. The need to balance the growing demand for nutritious food with these environmental threats is a complex issue, and ensuring sustainable food systems will require a collaborative effort from many different communities. These issues were addressed during the US-UK Scientific Forum on Sustainable Agriculture held in Washington, DC, on March 5-6, 2020. Organized by the National Academy of Sciences and the United Kingdom's Royal Society, the forum brought together leading scientists, researchers, policy makers, and practitioners in agricultural sciences, food policy, biodiversity, and environmental science (among other specialties). The forum provided an opportunity for members of these research communities to build multidisciplinary and international collaborations that can inform solutions to a broad set of problems. This publication summarizes the presentations of the forum.
Keywords: Environment and Environmental Studies; Agriculture

America's Geoheritage II: Identifying, Developing, and Preserving America's Natural Legacy: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
America is endowed with places that embody a rich geoheritage, from sites where indigenous people subsisted for millennia, to mines that furnished the raw materials that built U.S. industry, to mountain ranges and river gorges with unparalleled recreational opportunities, to field sites where students can truly understand a geological process, to places of aesthetic or spiritual value, and many more across all states and territories. In order to assess the status of geoheritage and the activities of its practitioners in the United States in light of social, political, and environmental changes over the past ten years, the National Academies of Sciences Engineering and Medicine convened a series of virtual webinars and a workshop. From September to December 2020, a Distinguished Speakers Webinar Program composed of eight webinars provided an overview of geoheritage initiatives, as well as focused presentations on geoheritage related to federal and state lands, cultural heritage, education, research, and economic development and geotourism. In January 2021, 101 land managers, state geologists, educators, researchers, and members and staff of professional societies and nongovernmental organizations participated in a virtual writing workshop to aggregate and organize community input on strategies and best practices in developing geoheritage sites across the United States. The participants were divided into focus groups that roughly aligned with the topics explored in the fall 2020 workshops. The groups worked synchronously and asynchronously over the course of a week, then presented their ideas in a plenary session. This publication summarizes the presentations and discussion of the webinars and workshop.
Keywords: Earth Sciences; Environment and Environmental Studies